Cost analysis of different cervical cancer screening strategies in Mexico - Christyn M Beal; Jorge Salmerón; Yvonne N Flores; Leticia Torres; Víctor Granados-García; Ellen Dugan; Eduardo Lazcano-Ponce (Instituto Nacional de Salud Pública, 2014)
Objective. To compare the costs and number of undetected cases of four cervical cancer screening strategies (CCSS) in Mexico. Materials and methods. We estimated the costs and outcomes of the following CCSS: a) conventional Papanicolaou smear (Pap) alone; b) high-risk human papilloma virus testing (HR-HPV) as primary screening with Pap as reflex triage; c) HR-HPV as primary screening with HPV-16/18 typing, liquid-based cytology (LBC) and immunostaining for p16/Ki67 testing as reflex triage, and d) co-testing with HR-HPV and LBC with HPV-16/18 typing and immunostaining for p16/Ki67 as reflex triage. The outcome of interest was high-grade cervical lesions or cervical cancer. Results. HR-HPV testing, HPV typing, LBC testing and immunostaining is the best alternative because it is the least expensive option with an acceptable number of missed cases. Conclusions. The opportunity costs of a poor quality CCSS is many false negatives. Combining multiple tests may be a more cost-effective way to screen for cervical cancer in Mexico